Exogenous Sucrose Supply Regulates the Physiological Index Levels Before the Flower Blooming and Fruit Abscission Stages in the Biodiesel Tree Sapindus mukorossi Gaertn. - Shilun Gao; Yuan Gao; Ying Yang; Liming Jia; Xuehuang Weng (HortScience, 2022)
Nutrient deficiency leads to a high fruit abscission rate and low yields of Sapindus mukorossi Gaertn. (Soapberry), which is one of the most widely cultivated biodiesel feedstock forests in China. Exogenous sucrose can provide a solution to nutrient deficiency and fruit abscission leading to low yields; therefore, it was applied to whole trees at two stages, 20 days before blooming (DBB stage) and before fruit abscission [days before fruit abscission (DBFA) stage]. Six sucrose concentrations, 0%, 1%, 1.5%, 3%, 5%, and 7%, were sprayed three times using a completely randomized block design with five replications and six treatments. 13CO2 labeling experiments were performed after the three sprayings. The results indicated that the 3% treatment had the highest yield, reaching 15.9 kg/tree. During the DBB stage, the 3% treatment significantly increased the inflorescence fructose and glucose contents 1- to 1.2-times and resulted in the highest fruit gibberellic acid, leaf indole acetic acid (IAA), fruit IAA, and fruit zeatin contents; however, it decreased the inflorescence abscisic acid (ABA) from 16 μg/g to 4 μg/g. The 1.5% and 3% treatments significantly increased the carbohydrate content and decreased the fruit ABA content to 30% to 50% of the control level during the DBFA stage. High-concentration sugar treatment (>3%) increased the nitrogen, phosphorus, and potassium contents, which decreased the calcium and magnesium contents. The 13C-dispatching ability of the inflorescence was three-times greater than that of leaves under the high-concentration sugar treatment during the DBB stage. Supplying 1.5% sucrose nearly doubled the allocation capacity during the DBFA stage. The source-sink nutrient migration pathway showed that leaf and fruit sugars were directly correlated with phosphorus. Fruit fructose and glucose contents affected the leaf mineral element contents.